A study on determinants of adopting Islamic banking products in Libya: the role of customer involvement and perceived usefulness as mediator - Albashir, Walid Ali (2019)
The purpose of this research is to identify the acceptance level of Islamic banking customers in Libya. Customers are confused due to various interpretations of Islamic banking in Libya and thus they are unable to make decision on the acceptance of Islamic banking. The research was conducted using the quantitative method, and self-administered survey questionnaire was used to gather information from Islamic banking customers. 293 customers with a response rate of 56.5% completed the survey that measured their use of Islamic banking and demographics. Structural equation modelling was used to examine the exploratory and confirmatory factor analysis of the instruments. The quantitative results revealed that subjective norms and perceived behavioural control are more significant to increase intention to use Islamic banking. The causal paths between the constructs of Theory of Planned Behavior (TPB) factors, customer involvement and perceived usefulness found significant indirect effect statistically. Customer involvement and perceived usefulness were found to be partially mediating between TPB factors and intention to use Islamic banking. Customer attitude and perceived risk was found to have no significant influence on intention at 0.05 level. With the significant standardized regression weights of all the constructs and items, the overall square multiple correlation was found to be 0.72 (72%) which is considered as very strong and significant finding of the study. Due to the ability to modify the theory of planned behavior model and approach to the research of intention, future researchers should consider the inclusion of variables that have influenced the relationship between intention and attitude of customers. Some consideration should be given to explore the impact of various external variables like demographic factors, security, organisational factors like management support, customer value and many others need to be considered. The lesson learned from the thesis is customer attitude and their involvement play a crucial role towards using Islamic banking products. Furthermore, it is the role of the bank managers to increase knowledge and awareness on Islamic banking products and reach out to customers providing information and benefits of Islamic banking and its products.